2020
DOI: 10.1186/s12870-020-02713-9
|View full text |Cite
|
Sign up to set email alerts
|

Different sets of TaCKX genes affect yield-related traits in wheat plants grown in a controlled environment and in field conditions

Abstract: Background TaCKX wheat gene family members (GFMs) encode the enzyme cytokinin oxidase/dehydrogenase (CKX), which irreversibly degrades cytokinins. The genes are important regulators of cytokinin content and take part in growth and development, with a major impact on yield-related traits. The goal of this research was to test whether these genes might be differentially expressed in the field compared to laboratory conditions and consequently differently affect plant development and yield. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(40 citation statements)
references
References 50 publications
1
24
0
Order By: Relevance
“…Therefore, in our work, the SNPs identified in the 4 high-yield soybean cultivars can conceivably diminish the activity of GmCKX14, and thereby enhance CK accumulation during the reproductive stages. This, would thus delay senescence, enhance photosynthesis and primordia formation, which, in turn, can increase the spike number, flower number and size, pod number, seed number and seed weight (Jameson and Song 2016;He et al 2018;Panda et al 2018;Szala et al 2020). Taken together, our data support the hypothesis that the substitution in GmCKX14 is closely linked to seed yield in soybean.…”
Section: Cytokinin Quantification By Hplc-ms/ms During Soybean Reprodsupporting
confidence: 81%
See 1 more Smart Citation
“…Therefore, in our work, the SNPs identified in the 4 high-yield soybean cultivars can conceivably diminish the activity of GmCKX14, and thereby enhance CK accumulation during the reproductive stages. This, would thus delay senescence, enhance photosynthesis and primordia formation, which, in turn, can increase the spike number, flower number and size, pod number, seed number and seed weight (Jameson and Song 2016;He et al 2018;Panda et al 2018;Szala et al 2020). Taken together, our data support the hypothesis that the substitution in GmCKX14 is closely linked to seed yield in soybean.…”
Section: Cytokinin Quantification By Hplc-ms/ms During Soybean Reprodsupporting
confidence: 81%
“…In plant species, CKX enzymes are produced by multi-gene families. Recently, progress has been made in identifying the mechanism of CKX gene family members (GFMs) to improve seed grain yield in several important crops, such as rice ( Oryza sativa L.) (Gao et al 2014; Gao et al 2019; Mao et al 2020), barley ( Hordeum vulgare L.) (Zalewski et al 2014; Holubová et al 2018; Gasparis et al 2019), and wheat ( Triticum aestivum L.) (Zhang et al 2012; Lu et al 2015; Chang et al 2015; Chen et al 2020), making CKX an emerging genetic target for crop yield improvement (Jameson and Song 2016; Szala et al 2020; Chen et al 2020). Considering the potential of CKX genes, Le et al (2012) identified and characterized expression of soybean CKX s at various plant development stages.…”
Section: Introductionmentioning
confidence: 99%
“…This is a possible reason for the weak progress in research on bread wheat compared to other cereals. TaCKX1, TaCKX2.2.1 and TaCKX2.2.2 are mainly expressed in developing spikes, TaCKX3 and TaCKX10 in seedling roots, TaCKX5, TaCKX9 and TaCKX8 in younger organs of developing plants from seedling roots to 0 days after pollination (DAP) spikes, and TaCKX11 and TaCKX4 in all organs [32,33]. Similar tissue specificity of expression of TaCKX GFMs was presented based on RNA-seq data [12], as well as for TaCKX1 and TaCKX2 during early kernel development [13].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in our work, the SNPs identified in the four high‐yield soybean cultivars can conceivably diminish the activity of GmCKX7‐1 , and thereby enhance CK accumulation during the reproductive stages. This, would thus delay senescence, enhance photosynthesis, and primordia formation, which, in turn, can increase the spike number, flower number and size, pod number, seed number and seed weight (He et al., 2018; Jameson & Song, 2016; Panda et al., 2018; Szala et al., 2020). Taken together, our data support the hypothesis that the substitution in GmCKX7‐1 is closely linked to seed yield in soybean.…”
Section: Discussionmentioning
confidence: 99%
“…In plants, CKX enzymes are produced by multi‐gene families. Recently, progress has been made in identifying the mechanism of CKX gene family members (GFMs) to improve seed grain yield in several important crops, such as rice ( Oryza sativa L.) (Gao et al., 2014, 2019; Mao et al., 2020), barley ( Hordeum vulgare L.) (Gasparis et al., 2019; Holubová et al., 2018; Zalewski et al., 2014), and wheat ( Triticum aestivum L.) (Chang et al., 2015; Chen et al., 2020; Lu et al., 2015; Zhang et al., 2012), making CKX an emerging genetic target for crop yield improvement (Chen et al., 2020; Jameson & Song, 2016; Szala et al., 2020). Considering the potential of CKX genes, Le et al.…”
Section: Introductionmentioning
confidence: 99%